Biodiversity conservation challenges in Wadi El-Gemal, Egypt: A Hotspot under pressure - A. Moustafa, Abdelraouf; Khalil, Yasmin; Khalaf, Menna; Elganainy, Roba; Zaghloul, Mohamed; Mansour, Samira; Hozzein, Wael; Alkhalal, Areej; Abd El-Ghani , Monier (Ecological Questions, 2026)
Wadi El-Gemal–Hamata Protected Area (WGHPA), located in the southeastern desert of Egypt along the southern Red Sea coast, represents a unique ecological system characterized by high biological diversity despite its arid environment. This study aimed to assess recent changes in the floristic composition of WGHPA in relation to anthropogenic pressures and climatic variability, while also providing an overview of the associated faunal diversity. Seasonal field surveys were conducted over two consecutive years (2022–2023) to document plant species, their life spans, growth forms, and conservation status, with complementary observations of vertebrate fauna and their conservation status. The floristic survey recorded a total of 77 plant species belonging to 31 families, with Amaranthaceae, Apocynaceae, Asteraceae, Fabaceae, and Zygophyllaceae representing the dominant families. Faunal surveys documented 73 animal species from 41 families, including birds, mammals, and reptiles, highlighting the importance of WGHPA as a habitat for rare, endemic, and migratory species. Field observations identified ecologically significant habitats, particularly wadis and mangrove stand, that function as biodiversity hotspots and play a crucial role in maintaining regional ecological balance. Despite its protected status, WGHPA is increasingly threatened by human activities, climate change, and unsustainable resource use. The findings underscore the need for integrated, ecosystem-based management strategies that balance conservation priorities with sustainable development. By documenting biological diversity and identifying key conservation areas, this study contributes to the sustainable management of WGHPA and supports broader conservation efforts for desert ecosystems in Egypt.